The development and applications of solar pond: a review - Abdulsalam, Alrowaished; Idris, Azni; Mohammad, Thamer A.; Ahsan, Amimul (Balaban Publishers – Desalination Publications, 2015)
Solar energy is a substantial source of clean and renewable energy. Recently, solar pond technology has made a great progress due to the fact that solar ponds can collect and store heat in the same time which has reduced the cost significantly thus making it an area of interest for the industry and researchers. Several salt gradient solar ponds have been constructed in many regions around the world. This paper reviews the various schemes of solar ponds, in addition to their performance, optimization, heat extraction mode and applications as reported in the literature. The maintenance and cost effect on solar pond have also been discussed.